A Cross-Sectional Survey on Cigarette Smoking in the Chinese Navy. Issue 5 (7th December 2018) - Chen, Fuxing; Hu, Pengwei; Chang, Wang; Chen, Chulin; Ding, Tianyuan; Liu, Xiaorong
Abstract: Introduction: The military is a risk environment for cigarette smoking. This study determined the prevalence of, cessation attempts, knowledge, and attitudes regarding smoking, and factors related to it in the Chinese navy. Materials and Methods: A cross-sectional survey was conducted of military personnel on active duty in the Chinese navy, Guangdong province. Data were collected using a standard structured questionnaire and analyzed through SPSS. Multiple logistic regression was used to examine factors associated with smoking. The research protocols were reviewed and approved by the Institutional Review Board of Naval Medical University, and participants gave written informed consent. Results: A total of 1, 530 military personnel who had served for >3 months completed the survey, 859 (56.14%) of whom were current smokers. The main reasons for smoking were stress alleviation and social needs. A total of 377 smokers had previously attempted quitting. More than half considered the military environment supportive of smoking. Subjects' knowledge regarding smoking mainly comprised negative respiratory-health effects. Smoking status was related to education level, military service duration, number of smoking family members, and smoking knowledge. Conclusions: Smoking prevalence in the Chinese navy is higher than that among Chinese civilians and the US and UK military personnel. Although many sailors are aware of the dangers of smoking to their health, they seldom get advice or help regarding smoking cessation. Most smokers believed that smoking cessation could improve their health. Therefore, the navy should formulate policies encouraging and facilitating military personnel's smoking cessation.